Numerical model validation for mengkulang glulam timber bolt withdrawal capacity - Shakimon, Mohd Nizam; Hassan, Rohana; Hassan, Mohamed Ali; Abd Malek, Nor Jihan; Mohamad Bhkari, Norshariza; Salit, Mohd Sapuan (Horizon Research Publishing, 2022)
The adequacy of timber joints determines how much load it can sustain, commonly called load-carrying capacity. European Yield Model (EYM), also known as Johansen yield theory, has been widely adopted in the design of timber joints for predicting load-carrying capacity. In EC5, the pulling out capacity is known as the 'rope effect' and becomes one parameter that governs the load-carrying capacity in a dowel-type timber connection. Due to the high cost of preparing the timber specimen, computer modelling always becomes the alternative in measuring the load-carrying capacity for timber connections. However, the computer modelling results need to be validated with the experimental laboratory test before being extended to different sizes and materials of fasteners. This study presents a finite element method (FEM) for numerical modelling and analysis to validate the experimental performance of timber's 12mm, 16mm, and 20mm bolt withdrawal capacity. This method adopted Abaqus 6.14.4 software package to create four (4) FEM models consisting of a bolt inserted into a glulam timber block at a different insertion depth, parallel and perpendicular to the timber grain direction. The axially inserted bolt was subjected to a pull-out force while the glulam timber block was held in position. The mild steel bolt and tropical Mengkulang glulam timber blocks were used. The validation showed an acceptable agreement between the FEM and the experimental results.